Training Cognitive Control in Older Adults with the Space Fortress Game: The Role of Training Instructions and Basic Motor Ability - Blumen, Helena M.; Gopher, Daniel; Steinerman, Joshua; Stern, Yaakov (Frontiers in Aging Neuroscience, 2010)
This study examined if and how cognitively-healthy older adults can learn to play a complex computer-based action game called the Space Fortress (SF) as a function of training instructions (Standard vs. Emphasis Change (EC); e.g. Gopher, Weil & Siegel, 1989) and basic motor ability. A total of 35 cognitively-healthy older adults completed a 3-month SF training program with three SF sessions weekly. Twelve 3-minute games were played during each session. Basic motor ability was assessed with an aiming task, which required rapidly rotating a spaceship to shoot targets. Older adults showed improved performance on the SF task over time, but did not perform at the same level as younger adults. Unlike studies of younger adults, overall SF performance in older adults was greater following standard instructions than following EC instructions. However, this advantage was primarily due to collecting more bonus points and not – the primary goal of the game – shooting and destroying the fortress, which in contrast benefitted from EC instructions. Basic motor ability was low and influenced many different aspects of SF game learning, often interacted with learning rate, and influenced overall SF performance. These findings show that older adults can be trained to deal with the complexity of the SF task but that overall SF performance, and the ability to capitalize on EC instructions, differs when a basic ability such as motor control is low. Hence, the development of this training program as a cognitive intervention that can potentially compensate for age-related cognitive decline should consider that basic motor ability can interact with the efficiency of training instructions that promote the use of cognitive control (e.g. EC instructions) – and the confluence between such basic abilities and higher-level cognitive control abilities should be further examined.